Pengaruh Sosialisasi Perpajakan, Pemahaman Perpajakan, Tarif Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Pada Pelaku E-Commerce di Shopee - Napisah Napisah; Khusnul Khuluqi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The study aims to examine the effect of tax socialization, understanding of taxation, tax rates and tax sanctions on taxpayer compliance in e-commerce at Shopee. The population used in this study were all questionnaires distributed via chat on the Shopee platform. The data used were collected based on voluntary sampling method and obtained a sample of 104 respondents. The method used in this study is a quantitative method using SPSS. The result in this study reveal that the variables of taxation socialization, understanding of taxation, and tax sanctions have no effect on taxpayer compliance in e-commerce at Shopee and tax rates affect taxpayer compliance in e-commerce at Shopee.